Прямий центральний співудар пружних циліндричних тіл: надзвуковий етап - Марченко, Т.А. (Видавничий дім "Академперіодика" НАН України, 2008)
An approach to the definition of characteristics of a direct central shock of two different elastic cylindrical bodies has been developed. It is supposed that bodies are made from different materials and have different masses and forms of the frontal surfaces. The contact area size changes while impacting and is directly determined during the solution. Shock is considered on a small time interval, during which the perturbation has no time to come to the free frontal surfaces of bodies (supersonic stage). The solution of the problem leads to the determination of key features of the shock interaction and their dependence on the shape of the frontal surfaces of bodies, their mass, and material characteristics.